Desigualdades sociais e evasão no ensino superior: uma análise em diferentes níveis do setor federal brasileiro - Gustavo Bruno de Paula (2021)
This research investigated the relationship between social inequalities and dropout from Brazilian federal public higher education, based on data of freshmen of the year of 2016. For this, the research design combines analysis of empirical quantitative and qualitative data, obtained from different levels: national level, covering the federal universities; institutional or local level, related to the Federal University of Minas Gerais – UFMG; and individual level, concerning interviews with undergraduates of this institution. Using information from the Higher Education Census, we verify if the dropout from the institutions is associated with the social origin of the students from the federal universities. Based on studies that point to the importance to differentiate the types of dropout, we applicate an innovative procedure separating the dropout from program or institution from the higher education system. Through descriptive statistics and logistic regression models with mixed effects, we observed that although, in general, the weak association between the socioeconomic variables and dropout, students from lower social background are more vulnerable to leave the higher education system, while their peers from more affluent social background have a higher probability of returning to other programs and institutions after they dropout. The data also showed that factors related to the types of programs are more important to the explanation of dropout than socioeconomic ones. Undergraduates of teaching or evening degrees, for example, have a higher probability of dropout not only from programs or institutions but also from the system. We applicate a similar design to study the data of undergraduates of UFMG. In this case, separating dropout from a program, followed by re-entry, and dropout from the institution. The results also indicated the weak influence of socioeconomics characteristics on dropout, especially from the institution, with factors related to the characteristics of the programs being more relevant. Based on these results, we pass to a more qualitative empirical analysis. From interviews with 12 undergraduates of the UFMG that left their programs or the institution, we identified that the socioeconomic characteristics were important to comprehend the reasons for their decisions to abandon the programs or the institution. Students from a higher social position left more voluntarily, for reasons linked to the loss of interest in the program or to seek alternatives seen as more satisfactory, while undergraduates of lower social position dropout more involuntarily, for academic difficulties or external responsibilities, like working, that harmed their permanence. The results indicate that even though the social origin does not significantly explain the probability of dropout from higher education, it is fundamental to understand its reasons. We conclude that is important to develop research designs that make it possible to distinguish the types of dropout and the reasons that lead students to leave higher education, to produce more effective social policies that aim to reduce the dropout processes that affects the more vulnerable and that constitute academic and social exclusion.